2013
DOI: 10.1007/s00270-013-0744-6
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Outcome of Endovascular Repair of Popliteal Artery Aneurysm Presents a Credible Alternative to Open Surgery

Abstract: The primary and secondary patency rates of endovascular repair of PAA are equivalent to the reported outcome of open repair. Reintervention and limb salvage rate appears better than open repair. With improved long-term outcomes, endovascular repair can be considered a credible treatment strategy for routine uncomplicated PAA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(40 citation statements)
references
References 17 publications
0
40
0
Order By: Relevance
“…There was no significant difference in primary patency for EVPAR compared with surgical repair, with a pooled HR of 1.30 (95% CI 0.79 to 12.14, p=0.189; Figure 2B). 14,15,18,21,24 A sensitivity analysis comparing primary patency in studies using both Hemobahn and Viabahn stent-grafts 14,20,21,23,25,26 compared to studies reporting Viabahn stent-grafts only [15][16][17][18][19]22,24,27 showed no significant difference in primary patency ( Figure 2C). …”
Section: Primary Outcomesmentioning
confidence: 99%
“…There was no significant difference in primary patency for EVPAR compared with surgical repair, with a pooled HR of 1.30 (95% CI 0.79 to 12.14, p=0.189; Figure 2B). 14,15,18,21,24 A sensitivity analysis comparing primary patency in studies using both Hemobahn and Viabahn stent-grafts 14,20,21,23,25,26 compared to studies reporting Viabahn stent-grafts only [15][16][17][18][19]22,24,27 showed no significant difference in primary patency ( Figure 2C). …”
Section: Primary Outcomesmentioning
confidence: 99%
“…The use of multiple stent grafts, moreover, has been already recognized as a predictor of complications. 7,8,10 In our experience, the mean discrepancy between the diameters of proximal and distal landing zones was 1.48 mm with a maximum value of 4 mm. We analyzed the results according to the discrepancy and, consequently, to the number of stent grafts implanted, but none of those parameters was found to be related to any difference in outcomes.…”
Section: Discussionmentioning
confidence: 96%
“…Because Marin et al 6 reported the first successful endoluminal treatment of a PAA with a stent graft in 1994, several single-center studies reported encouraging results. 7,8 In recent years, M€ ollenhoff et al 9 in their review assessed that endovascular repair of PAA with the Hemobahn/Viabahn endografts is a feasible, safe, and effective treatment; similarly, Saunders et al 10 reported similar primary and secondary patency rates of endovascular repair of PAA with respect to the reported rates of outcome of open repair. However, the deployment of a stent graft across a joint undergoing constant flexion increases the risk for graft migration, occlusion, or fracture.…”
Section: Introductionmentioning
confidence: 83%
“…Prospective RCTs comparing EVR and OSR are frequently called for in the literature. 9,27,39 However, the carrying out of valid randomized trials is complicated owing to the low prevalence rates of PAA, with long recruitment periods and divergent study populations. To provide a large number of patients and appropriate medical evidence, population based registries need to be established, such as the Swedvasc registry in Sweden, or the VASCUNET collaboration (Europe, Australia, New Zealand).…”
Section: Discussionmentioning
confidence: 99%